Securitization - A critical assessment in the light of the financial crisis - Marinova, Milena (2009)
My dissertation thesis provides a comprehensive analysis of the principles of securitization techniques, of their attendant shortcomings, their regulatory treatment and the recent proposals for reducing complexity in accounting standards with relevance for securitizations. The explosion of securitization and related innovative credit risk transfer products largely expanded the magnitude and diversity of issuers, investors and securities. With this expansion numerous market participants began to wrongly believe that risk was not only shared more widely, but also that it disappeared from the system altogether. The application, or to be more precise, the misapplication of securitization in the mortgage market had fatal consequences for the financial sector worldwide. Before securitization, sub-prime mortgage lenders retained the loans that they originated on their balance sheets and therefore cared about their credit quality. Securitization techniques and related innovative financial instruments enabled the export of sub-prime mortgage structural problems from the United States globe-wide via the financial intermediaries. More over, securitization techniques and related credit risk transfer products enabled single banks to reduce their individual risk while at the same time transferred new and greater risks to the financial system. Meanwhile a lot was written on the causes for the recent financial crisis. In most cases inadequate ratings provided by the credit rating agencies and different principal agent problems were addressed. I present both for completeness in my work. However, I argue that not only the credit rating agencies are to blame for the inadequate reflection of securitization and related financial innovations and subsequently for the financial turmoil. The international and national financial supervisors in fact supported the credit rating agencies to further establish their businesses.